2021
DOI: 10.3390/su13137045
|View full text |Cite
|
Sign up to set email alerts
|

The Idea of Corporate Social Responsibility in the Opinion of Future Managers—Comparative Research between Poland and Georgia

Abstract: The article deals with the issue of corporate social responsibility (CSR) in the awareness of economics students as future managers responsible for the implementation of this idea in enterprises. Due to the fact that CSR is a source of many innovations today, the aim of the research was to learn about the awareness and opinions of students about CSR on such issues as: reasons for implementation, main activities, impact on profitability, and the need to explore and assess the usefulness of this knowledge. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…Based on sustainable innovations, business models known as sustainable are created. These are all business models based on closed-loop [62], natural capitalism [63], CSR [64] social enterprises [65], product service systems (PSS) [66], and blue economy [67].…”
Section: Sustainable Business Modelsmentioning
confidence: 99%
“…Based on sustainable innovations, business models known as sustainable are created. These are all business models based on closed-loop [62], natural capitalism [63], CSR [64] social enterprises [65], product service systems (PSS) [66], and blue economy [67].…”
Section: Sustainable Business Modelsmentioning
confidence: 99%
“…This trend of neglecting certain aspects is often encouraged, especially for ideological reasons. This was verified in some districts that refused to shut down their industrial structures because they feared the loss of jobs [6,11,75,81,97]. Despite this, innovations in technology are now making possible an effective industrial conversion that saves jobs and worker identities and preserves a sense of community as well as the environment [26,60,[98][99][100][101].…”
Section: Discussionmentioning
confidence: 99%
“…Following the previously cited stakeholder theory [7,58,76], these kinds of organizations pursue an entrepreneurial strategy to consider the wider social impact [49,58,70,75,77,78], thereby reinforcing entrepreneurial resilience through stronger community approval (Entrepreneurship with link strength = 16 and occurrence = 10; Social Impact with link strength = 11 and occurrence = 7), which would help it to survive in a crisis. Knowledge with link strength = 9 and occurrence = 7) into a mindful entrepreneurial strategy [34,[79][80][81][82][83][84]. This can be realized through an exchange of knowledge [11,54,60] with university institutions [11,59,62,85], which creates the right combination between theory and practice.…”
Section: Cluster 2: Entrepreneurship and Social Impact (3 Items)mentioning
confidence: 99%
See 1 more Smart Citation
“…Some CSR studies found no difference between religious and non-religious managers; some established a negative impact of religious managers on CSR attitudes, whereas others showed a positive impact [9,11]. Nevertheless, these conflicting and mixed results agree that religious beliefs have a strong influence on workplace and personal values that affect CSR attitudes and behaviour [9,[12][13][14]. Both managers' beliefs and personal values are significant in shaping their managerial decisions and affect the values, beliefs, and behaviour of their followers [12,15].…”
Section: Introductionmentioning
confidence: 99%